Investigation into conditions of experimental observation of Borrmann effect in a parametric X-radiation - Blazhevich, S.V.; Noskov, A.V. (Вопросы атомной науки и техники, 2006)
Spectral-angular characteristics of coherent X-ray radiation of relativistic electrons in a crystal are formulated in
the framework of the dynamic theory of X-rays diffraction. Numerical calculations of the radiation angle density are
carried out for silicon and germanium single crystal to define the optimal experimental conditions of the anomalously
low photoabsorption (Borrmann effect) observation in the parametric X-radiation (PXR) with Bragg geometry.
The contribution of diffracted transition radiation is investigated depending on semi-infinite single crystal input surface
orientation relatively to definite set of its atomic planes. В рамках динамической теории дифракции сформулированы спектрально-угловые характеристики когерентного рентгеновского излучения релятивистских электронов в кристалле. Для кристаллов кремния и германия проведены численные расчеты угловой плотности излучения с целью определения оптимальных экспериментальных условий наблюдения аномально низкого фотопоглощения (эффекта Бормана) в параметрическом рентгеновском излучении в геометрии Брэгга. Исследован вклад дифрагированного переходного излучения в зависимости от угла ориентации входной поверхности полубесконечного кристалла относительно заданной системы его атомных плоскостей. У рамках динамічної теорії дифракції сформульовані спектрально-кутові характеристики когерентного
рентгенівського випромінювання релятивістських електронів у кристалі. Для кристалів кремнія і германія
проведені чисельні розрахунки кутової густини випромінювання з метою визначення оптимальних
експериментальних умов спостереження аномально низького фотопоглинання (ефекту Бормана) у
параметричному рентгенівському випромінюванні в геометрії Брегга. Досліджено внесок дифрагованного
перехідного випромінювання залежно від кута орієнтації вхідної поверхні напівнескінченного кристала
щодо заданої системи його атомних площин.